Child consumer deprivations: a study of children in relative poverty - Oliveira, Mayara Muniz; Pereira, Rita de Cássia Faria (Revista de Administração da UFSM, 2020)
The objective of this article is to analyze the material deprivations of child consumption in the context of relative poverty, in order to identify the deprivations experienced by children and to characterize the implications of and strategies for coping with these deprivations. In this empirical research, 23 children and their respective relatives were interviewed, totaling 46 interviewees. To collect data, a design technique was also employed through the production of a drawing by the child to support the interviews. The results indicate that children suffer deprivations related to health, education and housing. Deprivations concerning entertainment and toys were found more frequently. As a result of deprivation, children suffer emotional and social consequences, tackled through emotional reorientation.